Endovascular Treatment of Posterior Cerebral Artery Trunk Aneurysm: The Status Quo and Dilemma - Hou, Kun; Lv, Xianli; Yu, Jinlu (Frontiers in Neurology, 2022)
The posterior cerebral artery (PCA) is an important artery that can be divided into four segments (P1-4): segments P1-2 are proximal segments, and segments P3-4 are distal segments. Various aneurysms can occur along the PCA trunk. True saccular aneurysms are rare, and most PCA trunk aneurysms are dissecting. Sometimes, the PCA trunk can give rise to flow-related aneurysms in association with high-flow arteriovenous shunt diseases or moyamoya disease and internal carotid artery occlusion. Some PCA trunk aneurysms require treatment, especially ruptured or large/giant aneurysms. Recently, endovascular treatment (EVT) has become the mainstream treatment for PCA trunk aneurysms and mainly involves reconstructive or deconstructive techniques. Traditional EVT includes selective coiling with/without stent or balloon assistance and parent artery occlusion (PAO). For proximal aneurysms, the PCA should be preserved. For distal aneurysms, PAO can be performed. However, during EVT, preservation of the PCA must naturally be the prime objective. Recently, flow-diverting stents have been used and are a revolutionary treatment for unruptured dissecting aneurysms of the PCA trunk. Despite the associated complications, EVT is still an effective method for treating PCA trunk aneurysms and can result in a good prognosis.